The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.toxrep.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The combined fixed-dose antituberculous drugs alter some reproductive functions with oxidative stress involvement in wistar rats

Abstract: The reproductive toxicity of combined fixed-dose first-line antituberculosis (CFDAT) regimen was assessed in rats. Thirty-two (32) Wistar rats weighing 168.1 ± 8.0 g were divided into four groups of eight rats per group. Two groups of male and female rats were administered oral distilled water (1.6 ml) and CFDAT drugs containing rifampicin, isoniazid, pyrazinamide and ethambutol (RIPE, 92.5 mg/m2 per body surface area) respectively for forty-five days. Serum follicle stimulating hormone, luteinizing and testos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The observation of the effect of the FDC is similar to those of Awodele et al (2016) wherein they observed alteration of reproductive hormones in male and female rats when compared to the NC groups. Rifampicin is associated with hepatotoxicity mediated by oxidative damage ( Shanker et al, 2005 ; Chowdhury et al, 2006 ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The observation of the effect of the FDC is similar to those of Awodele et al (2016) wherein they observed alteration of reproductive hormones in male and female rats when compared to the NC groups. Rifampicin is associated with hepatotoxicity mediated by oxidative damage ( Shanker et al, 2005 ; Chowdhury et al, 2006 ).…”
Section: Discussionsupporting
confidence: 61%
“…Congestion of blood vessels suggests that the anti-TB drugs may have impaired venous outflow in the mice testes and thus, resulted in congestion. Awodele et al (2016) attributed decreased sperm counts and motility to choked vessels in the peri-testicular and Leydig cells of the stroma in the testes of rats exposed to the FDC and was linked to a reduction in male fertility. Testicular degeneration involves a retrogressive change in the germinal epithelium of the seminiferous tubules ( Macfarlane et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 54 , 55 Also, studies of positive stimulation by FSH and LH, which agreed with local paracrine signalling, have been reported. 54 , 56 This may, in part help maintains oestrogen secretion by the dominant follicle and thus, may provide such suitability for BSC to also be investigated in female species.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of the effect of RIF on reproduction and embryonic development is confined to only mammals, and these effects are equivocal in both male and female rats. The combined treatment of RIF with other anti-TB drugs such as ethambutol, isoniazid, and pyrazinamide in male rats causes an increase in oxidative damage with consequent suppression of the fertility index and lowers serum levels of Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH), and testosterone associated with lower sperm counts 18,19 . Similarly, RIF treatment reduces the quality of sperm chromatin structure and motility 20 , but increases testosterone levels in male rats by stimulating the production of 17-hydroxylase in the testes 21 .…”
Section: Introductionmentioning
confidence: 99%